RETRACTED: ORMDL3 Promotes Angiogenesis in Chronic Asthma Through the ERK1/2/VEGF/MMP-9 Pathway - Ding, Zhen; Yu, Fei; Sun, Yan; Jiao, Ning; Shi, Lina; Wan, Jinghong; Liu, Qinghua (Frontiers in Pediatrics, 2022)
ABSTRACT Aim：Angiogenesis plays an important role in airway remodeling in chronic asthma. ORMDL3 has been identified to be closely associated with the development of asthma remodeling. The goal of this study was to investigate the mechanisms of ORMDL3 in angiogenesis pathogenesis in the chronic asthma. Method: BALB/c mice were divided into three groups, including the asthmatic model group (group A), the budesonide-treated group (group B) and the normal control group (group C). HE and Masson staining were used to evaluate the pathological changes of lung tissue. Angiogenesis in lung tissue was examined by CD31staining.The expressions of ORMDL3, ERK1/2, MMP-9 and VEGF were examined. Furthermore, MMP-9 and VEGF mRNA levels were examined after the transfaction of BEAS-2B cells with the ORMDL-overexpressed lentiviral vector. Results: Compared with the control group, asthmatic model miceindicated more severe inflammation and airway angiogenesis with increased ORMDL3, ERK1/2, MMP-9 and VEGF expression. Budesonide alleviated airway angiogenesis and CD31 expression was positive with the levels of ORMDL3, MMP-9 and VEGF (P<0.01).The lentiviral vector overexpressing ORMDL3 was successfully constructed and effectively infected BEAS-2B cells. And ORMDL3 overexpression induced activated expression of VEGF and MMP-9 in vitro（P<0.01）. Conclusion: In conclusion, our study provided novel evidence that ORMDL3 promoted angiogenesis through upregulating VEGF and MMP-9 in chronic asthma.